(untitled) (UNWE Yearbook, 2020)
Human resources have a crucial role in each organization. They are very important with their skills, abilities, motivation, moral and attitudes. The achievement of business goals and business security goals as well depends on a great extent on human factor in the company. Business security goals are the recognition of threats, their prevention or elimination, or creating of opportunities for normal functioning of the business. The article presents the human factor’s positive and negative influence on the business security.